Prediction Activity Pharmacology and Molecular Docking of Secondary Metabolite Compounds of Tamarind Leaves (Tamarindus indica) as Anticancer - Muslikh, Faisal Akhmal; Riwanti, Pramudita; Alrayan, Reza (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2025)
Introduction: Cancer remains one of the leading causes of morbidity and mortality worldwide, with incidence and death rates increasing annually. One of the most effective therapeutic targets for cancer is the Epidermal Growth Factor Receptor (EGFR). However, the use of synthetic EGFR inhibitors is often associated with significant side effects. Aims: This study aims to evaluate the potential of compounds derived from Tamarindus indica (tamarind) leaves as anticancer agents through an in silico approach, including pharmacological activity prediction (PASS) and molecular docking against the EGFR receptor. Methods: Pharmacological activities were predicted using the Way2Drug webtool, while molecular docking analysis was performed using Molegro Virtual Docker (MVD). Result: The PASS prediction results indicated that the compounds in Tamarindus indica leaves possess a broad spectrum of anticancer activities. Docking analysis revealed that isovitexin exhibited the lowest rerank score among the test compounds and controls (erlotinib and the native ligand), indicating stronger binding affinity to EGFR. Conclusion: These findings support the potential of tamarind leaves, particularly isovitexin, as a promising computationally-predicted anticancer therapeutic candidate.